Prediction of mobile phone dependency based on shyness mediated by basic psychological needs among girl adolescents - Sara Ebrahimi (مطالعات اجتماعی روان‌شناختی زنان, 2023)
This study was conducted to investigate the moderated role of basic psychological needs by family cohesion in the relationship between shyness and mobile phone dependency among girl adolescents. It is a descriptive correlational research study. The study population included all girl adolescents aged 13 to 18, who were students in Tehran in 1401. 283 individuals were selected as a sample using the convenience sampling method and responded to the Revised Cheek and Buss Shyness Scale (Cheek, 1983), Mobile Phone Addiction Index (Leung, 2008), Basic Psychological Needs Scale (Deci & Ryan, 2000), and Family Organized Cohesiveness Scale (Fisher et al., 1992). Pearson correlation and multiple regression were used to analyze the data, and the Hayes macro-Process (model 4 & 59) in SPSS24 was installed. The results showed that basic psychological needs mediate the relationship between shyness and mobile phone dependency. The relation of shyness with mobile phone dependency and basic psychological needs, as well as the relationship between basic psychological needs and mobile phone dependence, is moderated by family cohesion. Based on this, by increasing the satisfaction of basic psychological needs in adolescents and increasing family cohesion, their shyness, and as a result, their dependence on mobile phones will decrease. These findings are useful for understanding the complex mechanism of shyness effects on mobile phone dependency and have practical implications for preventing and reducing adolescents' dependence on mobile phones. ‌